Pengembangan Pembelajaran Interaktif dan Budaya Membaca Sejak Dini untuk Meningkatkan Prestasi Belajar Siswa SDN Karangsengon 1 Bondowoso - Sima Lutfiyatus Sholehah; Novita Puri Rahayu; Nurul Musitah; Chelsea Titania Pratiwi; Berlianineva Putri Gani Evana; Muhammad Habibi Baiquni; Mailulah Ely Fauziyah; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the implementation of interactive learning development programs and the cultivation of a reading culture from an early age at SDN Karangsengon 1 Bondowoso to improve student learning achievement. The study uses a descriptive qualitative method with elementary school students and teachers as research subjects. The aim is to identify various strategies and activities that can encourage students to be more active and creative in the learning process. The program process includes various activities such as the application of interactive learning media, shared reading activities, word-composing competitions, and writing literacy activities, with literacy-based task score achievements. Data collection is carried out through structured observations, class participation checklists, and documentation of student activity results. The results show that the application of interactive learning can increase student activity, creativity, and enthusiasm in the learning process, while literacy activities gradually foster students' interest in reading and reading habits. The implementation of the program also has a positive impact on students' understanding of learning materials and learning attitudes. Therefore, developing interactive learning integrated with a reading culture from an early age can be an effective strategy for improving the quality of learning and learning achievement of elementary school students. The results are expected to provide real benefits in improving learning achievement and fostering a reading culture among students at SDN Karangsengon 1 Bondowoso.